2022
DOI: 10.3390/ijerph19042480
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenon of Social and Pastoral Service in Eastern Slovakia and Northwestern Czech Republic during the COVID-19 Pandemic: Comparison of Two Selected Units of Former Czechoslovakia in the Context of the Perspective of Positive Solutions

Abstract: This study seeks to explain the differences in the perception of social and pastoral service after the first and second wave pandemic in 2020 among the inhabitants of two neighbouring states, both parts of the former unified Czechoslovakia. Our research study compares subjective perception, needs, and participation among inhabitants of eastern Slovakia and north-western Czech Republic in social and pastoral service during the COVID-19 pandemic. The research sample consisted of a healthy population from the Cze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…During the COVID-19 pandemic, adolescents and children have not only been exposed to adverse social circumstances, but to effects on their mental health, well-being and (lack of) management of school responsibilities and homework [74,75]. This pandemic has greatly impacted education at all levels worldwide, with more than 290 million students affected by the shutdowns and a rapid face-to-face transformation towards e-learning [76]. This forced transition has raised the question of whether online education would foster inequalities and the challenge of meeting the United Nations Sustainable Development Goal for education [76], "ensure inclusive and equitable quality education and promote lifelong learning opportunities for all" [77,78].…”
Section: Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…During the COVID-19 pandemic, adolescents and children have not only been exposed to adverse social circumstances, but to effects on their mental health, well-being and (lack of) management of school responsibilities and homework [74,75]. This pandemic has greatly impacted education at all levels worldwide, with more than 290 million students affected by the shutdowns and a rapid face-to-face transformation towards e-learning [76]. This forced transition has raised the question of whether online education would foster inequalities and the challenge of meeting the United Nations Sustainable Development Goal for education [76], "ensure inclusive and equitable quality education and promote lifelong learning opportunities for all" [77,78].…”
Section: Educationmentioning
confidence: 99%
“…However, there are still some drawbacks associated with e-learning. For instance, the previous experience of the students in the use of ICMTs can affect their academic performance due to lower self-confidence, anxiety, or a higher need for time-management without the immediate help of instructors or classmates [76,82]. However, cultural, and socioeconomic reasons are the most important factors that can affect online education.…”
Section: Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…The consequence of the corruption of the public sphere is the disintegration of the community in its various aspects (Judák et al, 2022; Maturkanič et al, 2022a;Tkáčová et al, 2021a, b;) but above all as based on consensus derived from the social contract. A decent citizen has to wonder whether being decent is profitable for them.…”
Section: Depreciation Of a Human As A Beingmentioning
confidence: 99%
“…A Twitter poll showed that more than half of the respondents were sceptical about COVID-19 vaccinations [ 16 ]. Another study, that examined online search behaviour related to COVID-19 vaccines during the beginning of public vaccination, found that many individuals who are uncertain about critical vaccine-related information do not engage in active online search to address their information needs, highlighting the importance of encouraging more active information-seeking, as well as a critical appraisal of health information on the web, as a strategy for combating misinformation about COVID-19 vaccines [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%